Exploring Transformational Leadership in Fostering Student Entrepreneurship and Independence in Islamic Boarding Schools - Abidah Masrur; Moh. Syamsul Falah (Al-Qalam Institue, 2026)
This study aims to explore how transformational leadership contributes to the development of entrepreneurship and student independence within Islamic boarding schools. A qualitative single-case study design was employed. Data were collected through semi-structured interviews with five purposively selected informants, participatory observations, and document analysis. Data were analyzed using the Miles and Huberman interactive model, while trustworthiness was ensured through triangulation, member checking, prolonged engagement, and peer debriefing. The findings reveal that transformational leadership is manifested through the four dimensions of idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. Entrepreneurship development is facilitated through professional business management, structured internship programs, and the integration of Islamic values into organizational practices. Student independence emerges through interconnected personal, social, vocational, and financial competencies. Transformational leadership supports these outcomes by fostering character development, integrating entrepreneurial learning into educational activities, providing experiential learning opportunities, and implementing evaluation mechanisms that balance spiritual and managerial accountability. The study implies that transformational leadership can serve as an effective framework for integrating entrepreneurship education, character formation, and institutional sustainability within Islamic educational settings. It also highlights the importance of combining spiritual values with professional governance to strengthen student independence and support sustainable economic development.